Dynamic properties of denervated fast and slow twitch muscle of the cat - Kean, C. J. C. (1974)
1. Isometric and isotonic contractions were recorded from cat flexor digitorum longus (FDL) and soleus muscles denervated for 28-35 days and compared with the responses of contralateral control muscles. 2. Isometric twitch time to peak was longer in the denervated muscles than in the controls. Tetanic tension was reduced whether expressed as absolute units, per gram or per unit area. Absolute twitch tensions were reduced less below the control values with a consequent increase of twitch-tetanus ratio. These results agree with earlier reports; but, in contrast, there was no reduction in the relative rate of rise of tension in the isometric tetanus of denervated compared with control FDL. The maximum rate of rise of tension in the twitch was only a little less than that in the fully fused tetanus in the denervated muscles. 3. Whole muscle shortening velocity was reduced in the denervated soleus with no change in the number of sarcomeres per fibre. There was a smaller change in FDL muscles. This was the result of an increase in the number of sarcomeres per fibre which followed denervation in FDL, compensating for a decreased velocity of shortening of the sarcomere. Maximum sarcomere shortening velocity was reduced by 30% relative to control values in both muscles. 4. Measurements were made of the isometric contractions resulting from pairs of stimuli in an attempt to assess the period of maximal activation in the twitch. Maximum summation occurred when the second stimulus was given close to the time of the peak of the twitch in the denervated muscles.